2006
DOI: 10.7326/0003-4819-144-5-200603070-00013
|View full text |Cite
|
Sign up to set email alerts
|

Reporting Randomized, Controlled Trials of Herbal Interventions: An Elaborated CONSORT Statement

Abstract: Herbal medicinal products are widely used, vary greatly in content and quality, and are actively tested in randomized, controlled trials (RCTs). The authors' objective was to develop recommendations for reporting RCTs of herbal medicine interventions, based on the need to elaborate on the 22-item CONSORT (Consolidated Standards of Reporting Trials) checklist. Telephone calls were made and a consensus meeting was held with 16 participants in Toronto, Canada, to develop these recommendations. The group agreed on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
330
0
13

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 502 publications
(352 citation statements)
references
References 23 publications
1
330
0
13
Order By: Relevance
“…scandens preparations are very important step for clinical evaluation of herbal medicines (Gagnier et al, 2006). Since active ingredients in herbal products are influenced by several factors such as place, season or preparation, this may result in different clinical effects (Puttarak and Panichayupakaranant, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…scandens preparations are very important step for clinical evaluation of herbal medicines (Gagnier et al, 2006). Since active ingredients in herbal products are influenced by several factors such as place, season or preparation, this may result in different clinical effects (Puttarak and Panichayupakaranant, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Data extraction was undertaken by PP and RS using a data extraction form in accordance with the CONSORT statement for reporting herbal medicinal interventions (Gagnier et al, 2006). The data extracted included: study design; number of participants; age of participants; pain score of participants; characteristics of the intervention; and outcome measurement.…”
Section: Data Extraction and Quality Assessmentmentioning
confidence: 99%
“…62 The CONSORT extensions for reporting herbal medicinal interventions, 63 non-pharmacologic treatment interventions, 64 acupuncture interventions, 65 non-inferiority and equivalence trials, 66 and pragmatic trials, 67 will be used if relevant.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…The CONSORT organization works to standardize the way in which clinical trials are conducted, including the way in which results are reported. The organization recently published Reporting Randomized, Controlled Trials of Herbal Interventions: An Elaborated CONSORT Statement 3 . This important paper emphasizes the need for authentication of the product to be used in a clinical trial before that trial is started.…”
Section: Research On Nhpsmentioning
confidence: 99%
“…Quality-assured products are being developed through the same U.S. Food and Drug Administration (FDA) and Health Canada approval processes that are used for other drugs. Standards for the development and reporting of clinical trials of NHPs have been developed 3 . Many professionals involved in clinical research are currently involved in CAM studies.…”
Section: S54mentioning
confidence: 99%